Administrative Arrangement of Village Government in Poka Village, Teluk Ambon Subdistrict, Ambon City - Petronela Sahetapy; Zainal Abidin Rengifurwarin; Aminah Bahasoan; La Madjid; Humairah Almahdali; Zul Fadli (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This activity is an effort to improve the quality of village government services and efficiency in the management of government administration at the village level. Poka Village, located in Teluk Ambon Subdistrict, Ambon City, is one of the locations focused on in this activity. Various aspects of village government administration are analyzed and improved to ensure that the village can provide better services to its residents. This involves updates in population data management, financial administration, village development planning, as well as improvements in the implementation of information technology to support transparency and accessibility of village government information. Additionally, this activity also includes efforts to empower the village community in terms of participation in village decision-making, enhancing understanding of village governance, and involving residents in village development programs. The aim is to build a more inclusive, participatory, and democratic community in Poka Village. This Community Service aims not only to improve the quality of village government administration but also to have a positive impact on the daily lives of village residents. In this way, this activity contributes to improving the welfare of the village community, advancing local development, and creating a more empowered community that is aware of its rights and obligations in village governance.